LncRNA GACAT1 induces tongue squamous cell carcinoma migration and proliferation via miR‐149. Issue 17 (10th August 2021) - Wang, Xueling; Gong, Zuode; Ma, Long; Wang, Qibao
Abstract: Recent studies have observed that lncRNAs (long non‐coding RNAs) are involved in the progression of various tumours including tongue squamous cell carcinoma (TSCC). Recently, a new lnRNA, GACAT1, has been firstly identified in gastric cancer. However, its potential role in TSCC remains unknown. In this reference, we observed that GACAT1 was overexpressed in TSCC samples and cell lines. Of 25 TSCC specimens, GACAT1 expression was overexpressed in 18 patients (18/25, 72%) compared to non‐tumour specimens. Ectopic expression of GACAT1 induced cell growth and migration and promoted epithelial to mesenchymal transition in TSCC. In addition, ectopic expression of GACAT1 decreased miR‐149 expression in SCC1 cell. We observed that miR‐149 expression was down‐regulated in TSCC cell lines. Moreover, we observed that GACAT1 expression was negatively correlated with miR‐149 expression. GACAT1 overexpression induced TSCC cell growth and migration via regulating miR‐149 expression. These data provided that GACAT1 played an oncogenic role in the progression of TSCC partly through modulating miR‐149 expression.